License to Sell : The Effect of Business Registration Reform on Entrepreneurial Activity in Mexico - Bruhn, Miriam (MIT Press, 2012)
This paper estimates the economic effects of a recent reform that simplified business entry regulation in Mexico. The reform was introduced in different municipalities at different points in time. Using microlevel data, I find that the reform increased the number of registered businesses by 5%. This increase was due to former wage earners' opening businesses. Former unregistered business owners were not more likely to register their business after the reform. The reform also increased wage employment by 2.2%. Finally, the results imply that the competition from new entrants decreased the income of incumbent businesses by 3%.